CRITICAL FAILURE MODE ANALYSIS OF PROTON EXCHANGE MEMBRANE FUEL CELL USING FUZZY RISK PRIORITY CALCULATION AND PARETO RANKING - Brik, Kais; Yahmadi, Raja (Journal of Applied Engineering Science, 2026)
Fuel cell systems experience continuous performance degradation due to harsh operating conditions, which limits their durability and reliability. This paper therefore aims to examine the main causes and mechanisms of degradation affecting fuel cells, and in particular Proton Exchange Membrane Fuel Cells (PEMFCs), by conducting a detailed Failure Mode, Effects, and Criticality Analysis (FMECA). Each failure mode is assessed through the Fuzzy Risk Priority Number (FRPN), enabling the identification of the most critical degradation pathways. A Pareto-based classification is then applied to rank failure causes according to their contribution to system performance loss. The combined FMECA and Pareto approach makes it possible to highlight the dominant defects related to auxiliary components, flow regulation, sensor inaccuracies and the aging of the membrane and electrodes. Based on the critical causes identified, specific recommendations are proposed to improve reliability, including improved energy management and operating strategies, optimized control of pressure and humidity, and improved monitoring of auxiliary subsystems. The results provide a structured methodology for prioritizing degradation sources and guiding preventive maintenance and design improvements in fuel cell systems.